2013
DOI: 10.1186/1476-4598-12-151
|View full text |Cite
|
Sign up to set email alerts
|

TGM3, a candidate tumor suppressor gene, contributes to human head and neck cancer

Abstract: BackgroundIn our previous study using oligonucleotide microarrays, we revealed that transglutaminase 3 (TGM3) was remarkably down-regulated in head and neck cancer (HNC). However, the potential of TGM3 as a useful biomarker or molecular target for HNC is unclear.MethodsThe transcriptional and post-translational status of TGM3 in HNC cell lines and specimens was detected using real-time PCR and western blot analysis. Bisulfate-treated DNA sequencing was used to analyze the molecular mechanism of TGM3 gene silen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 42 publications
3
61
0
Order By: Relevance
“…TGM3 promoter CpG island hypermethylation has been observed in HNC and exogenous expression of TGM3 reduces tumor growth in vivo . Furthermore, low TGM3 expression is associated with poor overall survival [32]. There is also evidence for TGM3 to induce cell proliferation and migration in esophageal cancer by downregulating the NF-κB signaling pathway [33].…”
Section: Resultsmentioning
confidence: 99%
“…TGM3 promoter CpG island hypermethylation has been observed in HNC and exogenous expression of TGM3 reduces tumor growth in vivo . Furthermore, low TGM3 expression is associated with poor overall survival [32]. There is also evidence for TGM3 to induce cell proliferation and migration in esophageal cancer by downregulating the NF-κB signaling pathway [33].…”
Section: Resultsmentioning
confidence: 99%
“…The HNSCC cell lines were cultured in Dulbecco's Modified Eagle's Medium (Gibco, Carlsbad, CA, USA) supplemented with penicillin (100 U/ml), streptomycin (100 lg/ml) and 10% (v/v) heat-inactivated fetal bovine serum (FBS) (Gibco), as described previously [18]. All cells were incubated at 37°C in a humidified 5% CO 2 atmosphere.…”
Section: Cell Culturementioning
confidence: 99%
“…[ ] TGM3 expression is not restricted to skin; it also occurs in epithelia of tongue and oesophagus. While increase in tumor susceptibility has not been described in Tgm3‐/‐ mice, many human studies demonstrated the loss of TG3 expression associated with severity of tumors of epithelial origin (oesophageal or oral basal and squamous cell carcinomas) . Altered epithelial integrity due to the loss of TG3 may lead to increased inflammatory responses and drive a susceptibility to tumor progression.…”
Section: Mild or Functional Phenotypes In Genetically Engineered Tgm2mentioning
confidence: 99%
“…Besides inherited skin disorders and GRDs, a diversity of human pathologies have been associated with an underlying TG dysfunction (Table ). This involves diabetes, male subfertility, schizophrenia, hereditary spherocytosis, coagulopathies, age‐related cataractogenesis and tumor formation …”
Section: The Role Of Transglutaminases In Further Human Diseasesmentioning
confidence: 99%